2019
DOI: 10.1080/15324982.2019.1696423
|View full text |Cite
|
Sign up to set email alerts
|

Effects of biochar and peat on salt-affected soil extract solution and wheat seedling germination in the Yellow River Delta

Abstract: Salt-affected soils are widely distributed in arable croplands, so it is important to reclaim these soils. In this study, the effects of different biochar/peat doses (1, 3, and 5%) on 1:5 salt-affected soil: water extract solutions with different soil salinity levels after seven days shaking; and on winter wheat seedling growth after 80 hours are discussed. Results showed that the SAR and Cl-/SO 4 2ratio varied because of the changes of ion composition in the soil extract solution caused by the addition of bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 35 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…The root system of aquatic plants can also accumulate or produce a large number of nitrifying microorganisms to enhance the ability of water to degrade pollutants [49]. It was found that the amount and species of nitrifying bacteria in the pond environment with large plants were significantly higher than that out of plants [50]. In general, the content of nitrous nitrogen in crab breeding is less than 0.05 mg/L, indicating that aquatic plants inhibit the production of unstable N elements.…”
Section: Discussionmentioning
confidence: 99%
“…The root system of aquatic plants can also accumulate or produce a large number of nitrifying microorganisms to enhance the ability of water to degrade pollutants [49]. It was found that the amount and species of nitrifying bacteria in the pond environment with large plants were significantly higher than that out of plants [50]. In general, the content of nitrous nitrogen in crab breeding is less than 0.05 mg/L, indicating that aquatic plants inhibit the production of unstable N elements.…”
Section: Discussionmentioning
confidence: 99%
“…In pyrolysis, phytotoxic and carcinogenic compounds are released and heavy metals are transferred into less toxic forms; however, this depends on the feedstock type and pyrolysis conditions . The presence of PFR in BC induced negative impacts on plants, animals, and microbes by destabilizing membranes and causing oxidative damage. , Likewise, the presence of alkaline components in BC can increase pH and EC, which have negative impacts on plant growth. , . Further, nutrients from BC can also lost during pyrolysis, and the use of BC can also lead to an increase in greenhouse gas emissions.…”
Section: Limitations Of Using Biocharmentioning
confidence: 99%
“… 197 , 198 Likewise, the presence of alkaline components in BC can increase pH and EC, which have negative impacts on plant growth. 199 , 200 . 201 Further, nutrients from BC can also lost during pyrolysis, 202 and the use of BC can also lead to an increase in greenhouse gas emissions.…”
Section: Limitations Of Using Biocharmentioning
confidence: 99%
“…Meanwhile, water drawdown could be tolerated up to 60 cm. The study of Wang et al [46] showed that optimal yield of oil palm can be obtained at 40 to 60 cm of water depth. This condition is suitable to maintain surface moisture for preventing land fire.…”
Section: Land Suitability Assessment and Improvement Effortmentioning
confidence: 99%